A Bimetallic Metal–Organic‐Framework‐Based Biomimetic Nanoplatform Enhances Anti‐Leukemia Immunity via Synchronizing DNA Demethylation and RNA Hypermethylation. Issue 16 (12th March 2023) - Song, Yue; Zhang, Lingxiao; Wang, Yiqiao; Han, Mingda; Wang, Zhihua; Wang, Ning; Shao, Bingru; Li, Runan; Cao, Kunxia; Song, Meiyu; Du, Yangyang; Yan, Fei
Abstract: Epigenetic‐alterations‐mediated antigenicity reducing in leukemic blasts (LBs) is one of the critical mechanisms of immune escape and resistance to T‐cell‐based immunotherapy. Herein, a bimetallic metal–organic framework (MOF)‐based biomimetic nanoplatform (termed as AFMMB) that consists of a DNA hypomethylating agent, a leukemia stem cell (LSC) membrane, and pro‐autophagic peptide is fabricated. These AFMMB particles selectively target not only LBs but also LSCs due to the homing effect and immune compatibility of the LSC membrane, and induce autophagy by binding to the Golgi‐apparatus‐associated protein. The autophagy‐triggered dissolution of AFMMB releases active components, resulting in the restoration of the stimulator of interferon genes pathway by inhibiting DNA methylation, upregulation of major histocompatibility complex class‐I molecules, and induction of RNA‐methylation‐mediated decay of programmed cell death protein ligand transcripts. These dual epigenetic changes eventually enhance T‐cell‐mediated immune response due to increased antigenicity of leukemic cells. AFMMB also can suppress growth and metastases of solid tumor, which was suggestive of a pan‐cancer effect. These findings demonstrate that AFMMB may serve as a promising new nanoplatform for dual epigenetic therapy against cancer and warrants clinical validation. Abstract : A bimetallic metal–organic‐framework‐based biomimetic nanoplatform as a "nano‐epidrug" (AFMMB) is synthesized for improving anti‐leukemia immunity via dual targeting of DNA and RNA methylation. AFMMB selectively targets leukemic cells and induces autophagy. AFMMB increases the antigenicity of leukemia cells via upregulation of MHC‐I and downregulation of PD‐L1, which in turn enhances their recognition and killing by T cells.